PENGARUH PERSEPSI KUALITAS SIARAN DAN FORMAT SIARAN SERTA KUALITAS PENYIAR TERHADAP KEPUASAN DAN LOYALITAS PENDENGAR PADA RADIO KISS FM JEMBER - Sholihah, Dewi Deniaty (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract : This study aims to determine and analyze the significant influence the perceived quality of the broadcast, the broadcast format, and the quality of the broadcaster to the satisfaction and loyalty of listeners on Radio KISS FM Jember. This research is explanatory research and using survey methods. The study population was the whole KISS FM Radio listeners who live in Jember. The number of samples in this study of 108 respondents drawn using judgment sampling technique due to the nature of a heterogeneous audience. The data analysis method used is descriptive analysis and Structural Equation Model (SEM) with AMOS software tools. The results showed that the perceived quality of the broadcast, the broadcast format, and quality broadcaster significantly affect the satisfaction and loyalty of the KISS FM Radio listeners Jember.Keywords: Radio, Perceived Quality Broadcast, Broadcast Format, Broadcaster Quality, Satisfaction, Loyalty Listener.